Implementasi Pendidikan Implementasi Pendidikan Akal dalam Kurikulum Pendidikan Agama Islam Pada Tingkat Sekolah Dasar - Elmainetty, Harni; Arfian, Arfian - (Jurnal Ilmiah Wahana Pendidikan, 2023)
In Alquan, there are 49 repetitions that discuss 'aql, except for one, all of which are in the form of fi'il mudhar, especially material related to Wavu Jama'ah such as ta'qilun or ya'qilun. The verb ta'qilun is repeated 24 times and the verb ya'qilun is repeated 22 times. Although the verbs 'aqala, na'qilu and ya'qilu appear once each Reason is not just the power of the mind, the combination of all the powers of man which prevent him from falling into sin and error. That is why the Qur'an calls it the word "aql" (reason), which literally means "rope", which is what binds human passions and prevents them from falling into sin, mistakes, and mistakes. This study uses qualitative research methods with a qualitative approach. descriptive and data collection techniques using library techniques and literature studies. The results of this study are that in thinking humans should use the mind and heart. the power of the human mind is able to reach the physical area of ​​all relative problems, in contrast to the heart which has sharpness in terms of grasping meanings that have a metaphysical and absolute nature. Intellect Education in the Islamic Religious Education curriculum is an idea or notion that is structured in a curriculum document as a guide for educators in guiding, training, and forming students' critical, logical, systematic, and rational thinking skills so that they become human beings who have faith and are pious and have noble character. Keywords: Intellect, Reason Education, and Islamic Religious Education